The adventures of William Dampier with others who left Capn. Sharpe in the South Seas and travaled back over land through the country of Darien - Dampier, William (Adam Matthew Digital, 1681)
Ms. journal of William Dampier, 1681-1691, relating his adventures as a pirate in the South Seas following his departure from Bartholomew Sharp, and his journey overland with the help of Central American Indians